SCREENING FAKTOR RESIKO DIABETES MELITUS PADA INDIVIDU DENGAN RIWAYAT KELUARGA DIABETES MELITUS DI RSUD JAILOLO - Watta, Relin; Masi, Gresty; Katuuk, Mario E. (JURNAL KEPERAWATAN, 2020)
AbstractBackgroud: Diabetes mellitus is a chronic metabolic disorder characterized by an increase in blood glucose. The purpose of this study is to describe the risk factors for diabetes mellitus in individuals with a family history of diabetes mellitus. This method used a descriptive design with a Survey approach. The sample in this study were 100 people in family members who have a family history of diabetes mellitus. The test results obtained are a family history of diabetes mellitus with a high risk of 96 respondents (96%). The description of knowledge on high-risk eating patterns was 80 respondents (80%), while attitudes toward eating patterns show 81 respondents (81%) were at high risk. The description of knowledge about physical activity shawed that 76 respondents (76%) had a high risk, while the attitude towards physical activity showed 37 respondents (37%) had a high risk and 63 respondents (63%) had a low risk. Conclusion there is a high risk of diabetes mellitus in individuals with a family history of diabetes, most respondents have low knowledge and attitudes about eating patterns so that they have a high risk of diabetes, and respondents' knowledge about high-risk physical activity but attitudes to low-risk physical activity.Keywords: Screening, Risk factors, Diabetes mellitusAbstrakLatar belakang: Diabetes melitus adalah penyakit gangguan metabolisme kronis  yang ditandai dengan peningkatan glukosa darah. Tujuan penelitian diketahui gambaran faktor resiko diabetes melitus pada individu dengan riwayat keluarga diabetes melitus . Metode penelitian deskriptif  dengan metode Survey. Sampel dalam penelitian ini adalah 100 orang pada anggota keluarga yang memiliki riwayat keluarga diabetes melitus. Hasil hasil uji diperoleh yaitu gambaran riwayat keluarga diabetes melitus yang beresiko tinggi sebanyak 96 orang responden (96%). Gambaran pengetahuan pada pola makan yang beresiko tinggi sebanyak 80 orang responden (80%), sedangkan  sikap pada pola makan menunjukan  81 orang responden (81%) beresiko tinggi. Gambaran  pengetahuan tentang aktivitas fisik menunjukan 76 orang responden (76%) beresiko tinggi, sedangkan sikap pada aktivitas fisik yang menunjukan 37 orang responden (37%) beresiko tinggi dan  63 orang responden (63%) yang beresiko rendah. Kesimpulan terdapat resiko tinggi diabetes melitus pada individu dengan riwayat keluarga diabetes, sebagian besar responden memiliki pengetahuan dan sikap yang rendah tentang pola makan sehingga memiliki resiko tinggi terhadap diabetes, dan pengetahuan responden tentang aktivitas fisik beresiko tinggi tetapi  sikap pada aktivitas fisik  beresiko rendah.Kata Kunci : Screening, Faktor Resiko, Diabetes Melitus.